Hepatic recovery after damage produced by sub-chronic intoxication with the cyanotoxin microcystin LR - Andrinolo, Darío (2008)
The effect of sub-chronic exposure of intraperitoneal (i.p.) injections of microcystin-LR (MC-LR) on microscopic tissue architecture, hepatic function and lipid peroxidation has been studied in liver and kidney of mice. Mice were treated i.p. with 25 mg of pure MC-LR/kg body weight or saline solution for 1 month (every 2 days) with the aim of producing an inflictive stage with evident damage. Histopathological analysis of dissected livers of mice showed a disrupted lobar architecture and the development of cytoplasmatic vacuoles. According to this, a significant increase in hepatic lipid content and in lipid peroxidation levels in liver and kidney was found in MC-LR-treated animals when compared with controls. Moreover, serum alkaline phosphatase and aspartate aminotransferase activities showed a significant alteration in MC-LR-treated animals. After damage, progression or recovery was studied for 1 and 2 months of wash-out. The recovery from liver damage was evident at the cytological and physiological level, only the recovery of lobar architecture was incomplete along the period investigated. In conclusion, the present study demonstrates the ability of hepatic tissue to recover from damage produced by sub-chronic MC-LR administration. The dynamic interplay between damage and tissue-repairing response in determining the ultimate outcome of toxicity should be considered in risk-assessment studies.